KETERKAITAN ANTARA KETERSEDIAAN PELAYANAN DASAR PENUNJANG PERMUKIMAN PERKOTAAN DAN GUNA LAHAN PERMUKIMAN (Studi Kasus: Kecamatan Rangkasbitung, Banten) - Purba, Sabrina; Permana, Chrisna Trie Hadi; Pujantiyo, Bambang S. (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2024)
Rapid urbanization has become a significant global phenomenon, affecting not only major cities but also suburban areas, with profound impacts on various aspects of urban life. This article explores the correlation between the increase in population as an impact from urbanization and the availability of basic services in Rangkasbitung, which consists of 16 villages. The purpose of this research is to determine the effect of the availability of basic daily services on the amount of residential land use in Rangkasbitung. Basic services are assessed using the 20-Minute Neighbourhood parameter, which represents an area designed to provide essential services within a short walk for residents. This research uses quantitative descriptive methodology, with spatial analysis and descriptive statistical analysis. The study is limited to the availability of residential land use, basic services, and public transportation as the three main components in the development of urban residential areas based on the 20-Minute Neighbourhood parameter. The 20-Minute Neighbourhood is a city planning concept defined as an area where residents can access most activities necessary for a good life without traveling outside the area. The results indicate that the availability of basic services in an area affects residents' decisions on where to live.